Benefits of lactate testing
Lactate testing enables a coach to : - develop individual training programs for each athlete that reflect the actual stress being put on the athlete's metabolism.. - monitor and evaluate the effect of these training programs on a athlete's metabolism. - determine if the athlete is producing too much or too little lactate during a set. - know if each athlete's ability to clear lactate is improving or deteriorating.. - educate and motivate athletes.